PSYCHOSOMATIC DISORDERS OF THE ENDOCRINE SYSTEM IN CHILDREN OF THE MOUNTAINOUS AREAS - Semak, Оlena (Mountain School of Ukrainian Carpaty, 2018)
The paper aims at determining the prevalence of psychosomatic disorders of the endocrine system in children living in mountainous areas, as well as at analyzing their connection with cultural traditions and living conditions. The author declares an important role of the psychological factor in the occurrence of bodily diseases. The theoretical analysis of the problem was carried out in the work: the main psychological mechanisms of the formation of diseases are described; the data on known causes of psychosomatic disorders of children are generalized; the meaning of emotional influences at an early age is explained. Existing results of clinical studies on the prevalence of endocrine diseases in mountainous areas (insular diabetes, hypothyroidism, hyperthyroidism, impaired puberty and metabolic disorders) are provided, and their interpretation is given in terms of psychogenic causes. The complex environmental and social conditions of life in the Ukrainian Carpathians, which lead to the formation of peculiar individual traits and behavioral patterns of mountaineers, are analyzed in detail. On this basis, specific mechanisms of occurrence of psychogenic diseases of children living in mountainous areas are named: limited social contacts, low level of general competence, lack of maternal attention and lack of educational influence of parents, dependence on the environment, excessive early demands on the independence of children, their engagement in adult activity, apathy, loss of purpose-in-life orientations, etc. The conclusion about possible directions of the corresponding psychoprophylaxis is substantiated.